ANALISIS KESENJANGAN DAN PERBANDINGAN KAYU PAPI R.Br) DENGAN CENDANA ( Linn.) DI NUSA TENGGARA TIMUR, INDONESIA - Aziz Umroni; Heny Rianawati; Siswadi Siswadi (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2015)
Shrub sandalwood (Exocarpus latifolia R.Br) is potential for the substitution of sandalwood (Santalum album Linn.). The rising demand and ineffective regulations increase threats toward its sustainability. This research aimed at: 1) conducting gap analyses of information and conservation between sandalwood and shrub sandalwood and 2) comparing production, price and abundance of both species. Analysis 1 used literature review and comparison study while analysis 2 used Importance Value (IV) and comparison. The results showed that: Firstly, there is a significant disparity of information and conservation between both species, i.e there are 319 scientific publications related to sandalwood and four conservation plots have been built, meanwhile only 10 scientific publications about shrub sandalwood and only one conservation plot has been settled; Secondly, the price of shrub sandalwood (IDR 3.15 million/m ) is lower than sandalwood (IDR 225 million/m ) and the average production (2009-2012) of shrub sandalwood (700 m annually) is higher than sandalwood (166 m annually); Thirdly, the abundance of shrub sandalwood in several forests in Timor is lower than sandalwood, i.e IV at poles and trees of shrub sandalwood are 31-58 and 9-32 respectively, while for sandalwood are 194-234 and 60-209 respectively. The less stands in their habitats and relatively higher wood production indicated that shrub sandalwood is more endangered than sandalwood.